A critique of the blueprint on education for the gifted and talented persons in Nigeria (2010)
A blueprint is a springboard for achieving target goals in any given endeavor. In 1986 a blueprint was prepared by the National Planning Committee on Education for the Gifted and Talented Children in Nigeria. Any form of defect recorded while formulating the blueprint will automatically affect goal achievement. It is against this background that the writer highlights all the inadequacies in the blueprint after which a position is taken with the belief that all the anomalies will be rectified and the desired goal will still be realized. Finally, considering the multi-modal nature of gifted education programme, the writer is of the opinion that the financial implications of running the programme are far reaching. It is therefore recommended that both the public and private sectors should team up with the three tiers of Government and be adequately involved in its funding.